Penerapan Modeling Transportasi Sebagai Dasar Penyusunan Rencana Induk Jaringan Jalan - Rahayu Sulistyorini (UNIVERSITAS LAMPUNG, 2012)
In the development of transportation, government had role as guidance, so they have obligated toprepare and formulated transportation policy, control and monitor implementation of transporta-tion. One obligation referred to is setting transportation infrastructure network and level of ser-vice. Other important thing is performing prediction the movement of passengers and goods espe-cially on each point of transportation movement, related to road network master plan.The main objective of this research is the application of modeling transport in road network plan-ning. Other policies that will follow are the settings and policies regarding to freight circulation interminal, the recommendation of public transport and road network system. Four stages of trans-portation planning is used as a research method.The result of this study is recommendation that necessary to preserve transportation service in ru-ral areas to develop primary transportation based on community and land use development. Rec-ommendation of road network master plan is resettle of road level and function based on activity,new corridor development connecting under development area and nationality conection.